Correlation analysis between micro and macro indicators of high modulus modified asphalt for asphalt pavement - Jiarong Wang; Zhengqi Zhang; Zhongnan Tian (PLoS ONE, 2025)
The relationship between the micro technical indexes and the macro road performance of high modulus asphalt (HMA) is helpful for understanding its mechanism and performance, and promoting its application. To explore the relationship, two kinds of high modulus asphalt (HMA), LLDPE/SBS composite modified asphalt and rubber/PPA composite modified asphalt were prepared according to the HMA requirements. Secondly, Molecular models of two kinds of HMA were established through molecular dynamics (MD) simulations, and the high temperature parameters of LLDPE/SBS composite modified asphalt were obtained with the two methods, namely the micro molecular dynamics simulation and high temperature rheological test, respectively. Then, through correlation analysis and regression calculation, the estimation formula was established between the results of molecular dynamics simulation and high temperature rheological test. Finally, in order to evaluate and verify the rationality of the estimation formula, the two methods were carried out on the other HMA (rubber/PPA composite modified asphalt). The results show that the shear modulus obtained by molecular dynamics simulation has a good correlation with the high temperature rheological properties. The estimation formula based on molecular dynamics simulation can be used to estimate the high temperature shear modulus of high modulus asphalt, and the relative error is less than 7%, which means that the formula can be used to effectively predict the high temperature performance of high modulus asphalt.